Describe the transformation of f(x)=5x that produces g(x)=-2(5x-1)?
- PopeLv 74 weeks ago
y = g(x)
y = -2(5x -1)
y = -2(5x) + 2
y = -2f(x) + 2
The graph of y= f(x) undergoes these two transformations in order:
Scale vertically by factor -2, with the x-axis invariant.
Translate upward two units.
There are many ways of building the same net transformation. This answer does not conflict with the one you received earlier. I am only putting in a form more familiar to me.
- ?Lv 74 weeks ago
f(x) = 5x ⇢ shift f(x) down by 1 unit ⇢ f₁(x) = 5x-1
⇢ flip f₁(x) across x-axis ⇢ f₂(x) = -(5x-1)
⇢ scale f₂(x) by a factor of 2⇢ g(x) = -2(5x-1)